Maternal serum screening in Newfoundland and Labrador: Do attitude and knowledge affect physicians’ practice? - Cavanagh, Jonathan (College of Family Physicians of Canada, 2006)
OBJECTIVE: To examine family physicians’ practice of, attitudes toward, and knowledge about maternal serum screening (MSS) and to compare the demographic and practice characteristics, attitudes, and knowledge of physicians who offer MSS to all their pregnant patients with those of physicians who offer MSS to some or none of their pregnant patients. DESIGN: Cross-sectional mailed survey. SETTING: Newfoundland and Labrador. PARTICIPANTS: One hundred eighty-two family physicians who provided prenatal care. MAIN OUTCOME MEASURES: Proportion of physicians offering MSS to their pregnant patients. Sociodemographic characteristics and attitudes toward and knowledge about MSS of physicians who offer MSS to all, some, or none of their pregnant patients. RESULTS: Just over half the physicians (52.2%) offered MSS to all their pregnant patients, 34.6% offered it to some patients, and 13.2% did not offer MSS at all. Almost two thirds of physicians (63.6%) had not changed their practice regarding MSS in the past 18 months, but 29.5% said they offered MSS more often. About 69.6% of physicians communicated positive results to patients within 48 hours; 60.8% communicated negative results at the next clinical appointment. Half (50.6%) believed that offering MSS did not affect their legal risk, 24.1% said it increased their risk, and 25.3% said it decreased their risk. Most physicians (83.4%) ordered MSS at the correct gestational age. A larger proportion of those who offered MSS to all patients were female, were between 30 and 39 years old, had graduated from Canadian medical schools, practised in urban centres, and were aware of the provincial MSS program. Physicians who offered MSS to all, some, or none of their patients were similar in terms of length of practice in Canada, whether they performed deliveries, number of pregnant women they cared for annually, beliefs about MSS and legal risk, and general knowledge of MSS detection rates. CONCLUSION: More than half the family physicians in Newfoundland and Labrador offered MSS to all their pregnant patients, and another third offered it to some patients. Physicians’ practice was not related to their attitudes toward or knowledge about MSS.